2021
DOI: 10.33578/pjr.v5i2.8246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Dictogloss on Students’ Listening Comprehension Achievement

Abstract: Listening is one of the most important skills which should be had by students of English as foreign language. Listening has a vital part in learning foreign language especially in term of communication because many of students’ activities are used to listen. However, students’ listening comprehension has not met good result yet. This study was conducted to find out the impact of using dictogloss in improving students’ listening comprehension achievement. The design of this study was a quasi-experimental study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…The results of the current study are consistent with other studies that revealed the efficacy of deploying dictogloss in enhancing some EFL learners' skills (Aminatun, Muliyah & Haryanti, 2021 Khorrami ,2020;Kurtaj, 2021;Putri ,2020;Rashtchi, 2020;Zinkgraf & Verdú ,2021;Zohrabi & Tahmasebi ,2020).…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the current study are consistent with other studies that revealed the efficacy of deploying dictogloss in enhancing some EFL learners' skills (Aminatun, Muliyah & Haryanti, 2021 Khorrami ,2020;Kurtaj, 2021;Putri ,2020;Rashtchi, 2020;Zinkgraf & Verdú ,2021;Zohrabi & Tahmasebi ,2020).…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…The dictogloss technique may be used with a variety of texts, such as brief snippets from newspapers, academic literature, narratives, or texts developed specifically by teachers for the purpose of facilitating particular learning outcomes (Syafiq, 2021;Rangkuti, 2021) In recent years, an expanding body of research has grown, focusing on investigating the effect of the dictogloss technique on multiple aspects of EFL instruction. These aspects include skills, i.e., listening (Tsauri, 2021;Aminatun, 2021), speaking skills (Rahayu, 2020;Rashtchi, 2020), writing skills (Sugondo, 2021), and other aspects, particularly grammar (Kurtaj, 2021), self-learning (Lim, 2021), motivation ( 2021), and perceptions ( Kim & Cha, 2021) One main common ground among aspects of the dictogloss technique and web-based learning is that the learning process encompasses more than a passive reception of information from the teacher. It involves active engagement by students through activities such as watching, demonstrating, and other associated tasks.…”
Section: The Use Of Dictogloss Youtube Videos For Enhancing English L...mentioning
confidence: 99%
“…According to Mandasari and Oktaviani (2018), they stated that by employing any kinds of techniques to learn a language namely listening to English sound, memorizing the vocabulary, describing images and watching films are such an effective way to learn English. Listening is one skill that also plays important role in the process of learning pronunciation and speaking (Kuswoyo and Wahyudin, 2017;Mandasari and Aminatun, 2020;Aminatun et al, 2021). Starting from listening to the music and seeing the lyrics, students will be able to use their memory to learn English.…”
Section: Introductionmentioning
confidence: 99%
“…Motivasi belajar yang rendah akan berdampak serius pada siswa yang nantinya tidak memiliki antusiasme dalam belajar bahasa Inggris, dan pada akhirnya akan mempengaruhi prestasi siswa (Aminatun, Muliyah & Haryanti, 2021).…”
Section: Permasalahan Mitraunclassified